Optimization of infusional calcium gluconate for prevention of hypocalcemic reactions during therapeutic plasma exchange. Issue 6 (10th August 2019) - Zhao, Yong; Garrity, Danielle; Graves, Molly; Linden, Jeanne; St. Pierre, Patricia; Ducharme, Paula; Greene, Mindy; Vauthrin, Michelle; Weinstein, Robert
Abstract: We sought to optimize direct intravenous infusion of calcium gluconate (CaGlu) for maintaining plasma ionized calcium concentration ([Ca 2+ ]) and preventing hypocalcemic reactions during 34 consecutive 1‐volume therapeutic plasma exchanges (TPEs) in eight patients. CaGlu, 2 g in 50 mL of 0.9% NaCl, was prepared by our hospital pharmacy and infused at either 1.0 or 1.6 g/h during alternate TPE. Plasma [Ca 2+ ] was monitored at intervals of 20 to 30 minutes. At 1 g/h of CaGlu, plasma [Ca 2+ ] fell by 8.35% after 40 to 50 minutes and then plateaued. At 1.6 g/h of CaGlu, plasma [Ca 2+ ] fell by 6% after 20 to 30 minutes and then plateaued. The difference at 40 to 50 minutes was significant ( P = .015). Hypocalcemic reactions were noted in three patients during 5 of 17 TPE at 1.0 g/h (all after 40 to 60 minutes) but 0 of 17 TPE at 1.6 g/h ( P = .044). CaGlu at 1.6 g/h stabilized plasma [Ca 2+ ] and appears to prevent hypocalcemic reactions during TPE.